Association of gadget use with learning focus and interpersonal skills among school-age children: A cross-sectional study - Setiawati, Peni; Arsi, Ranida; Rimbawati, Yazika (Lentera Perawat, 2026)
Background: The increasing use of digital technology has expanded gadget exposure among school-age children, which may influence learning concentration and social interaction development in educational settings. Educational stakeholders therefore require empirical evidence to understand how gadget use relates to learning focus and interpersonal skills. Objective: This study aimed to examine the association between gadget use, learning focus, and interpersonal skills among school-age children. Methods: A quantitative cross-sectional correlational design was employed. The study involved 60 students in grades IV and V at MI Najahiyah Seberang Ulu 1, Palembang, Indonesia, selected through purposive sampling based on predefined inclusion criteria. Data were collected using structured questionnaires measuring gadget use, learning focus, and interpersonal skills. Descriptive statistics were used to summarize respondent characteristics, while Spearman’s rho correlation test assessed associations between variables at a 95% confidence level. Results: The findings showed a statistically significant association between gadget use and learning focus (p < 0.001; r = 0.792) as well as between gadget use and interpersonal skills (p < 0.001; r = 0.764). Most respondents demonstrated moderate gadget use, generally high learning focus, and predominantly good interpersonal skills. These results indicate that variations in gadget use levels are closely related to differences in cognitive concentration and social interaction abilities among school-age children. Conclusion: Gadget use shows a significant association with learning focus and interpersonal skills among school-age children. Balanced and supervised gadget use is essential to support optimal academic engagement and social development.